DEBUS (Early Bullying Detection) Training to Improve the Knowledge and Ability of Adolescent Cadres in Detecting Bullying Situations - Sandra, Gabrillah Mullah; Alfian, Ilham Nur (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Bullying is believed to be behavior that cannot be avoided and commonly occurs in school-aged children. Especially for children who are in poverty and living in slums, their risk of becoming aggressive and carry out bullying is higher due to the influence of their culture and environment. The research participants were members of the Sanggar Alang-alang community, most of whom live in Joyoboyo, which is a risky environment. The aim of this research is to form a cadre of teenagers who can detect bullying situations so that they can independently find out, analyze and report the situation to their caretaker or others with more authority. The research method is quasi experiment with a quantitative and qualitative approach. Quantitative data (n=7) was obtained from pre and post-test questionnaires to determine changes in knowledge after being given the intervention. Furthermore, qualitative data was obtained through semi-structured interview methods and case studies to determine field data, responses and implementation of the interventions provided. The intervention was carried out using psychoeducational training techniques given to selected teenagers from the members of the community. The results of the research showed that there was a significant difference in knowledge before and after the training (p=0.114). From the qualitative data, the participants showed the ability to detect, identify and analyze bullying situations and behaviors. They were also enthusiastic about becoming supervisory cadres in the community to channel the knowledge and skills they have gained. Based on these results, the DEBUS (Detecting Bully at Early Age) training is effective in increasing knowledge about bullying and giving the participants skills to detect bullying situations.Bullying dipercayai sebagai perilaku yang tidak bisa dihindari dan biasa terjadi pada anak usia sekolah. Khususnya pada anak yang berada dalam kemiskinan dan hidup di lingkungan kumuh, risiko mereka untuk menjadi agresif dan melakukan bullying lebih tinggi karena pengaruh dari lingkungan dan budaya mereka. Partisipan penelitian adalah anggota komunitas Sanggar Alang-alang yang sebagian besar hidup di Joyoboyo yang merupakan lingkungan berisiko. Tujuan penelitian ini yaitu membentuk kader remaja yang bisa mendeteksi situasi bullying agar mereka bisa secara mandiri mengetahui, menganalisis dan melaporkan situasi tersebut ke pendamping atau orang yang lebih berwenang. Metode penelitian yang dilakukan adalah quasi experiment dengan pendekatan kuantitatif dan kualitatif. Data kuantitatif (n=7) diperoleh dari kuisoner pre dan post-test untuk mengetahui perubahan pengetahuan setelah diberikan intervensi. Selanjutnya, data kualitatif didapatkan melalui metode wawancara semi terstruktur serta studi kasus untuk mengetahui data lapangan, respon dan implementasi dari intervensi yang diberikan. Intervensi dilakukan dengan teknik psikoedukasi pelatihan yang diberikan pada remaja terpilih dari anggota sanggar. Hasil dari penelitian menunjukkan bahwa terdapat perbedaan pengetahuan yang signifikan sebelum dan sesudah dilakukan pelatihan (p=0,114). Secara kualitatif, subjek menunjukkan kemampuan dalam deteksi, identifikasi, dan analisis situasi dan perilaku bullying. Mereka juga antusias untuk menjadi kader pengawas di sanggar untuk menyalurkan pengetahuan dan kemampuan yang mereka dapatkan. Berdasarkan hasil tersebut, pelatihan DEBUS (Deteksi Bully Sedari Dini) yang dilakukan efektif dalam meningkatkan pengetahuan tentang bullying serta memberikan subjek penelitian keterampilan untuk melakukan deteksi situasi bullying.